Peranan Penyuluh Menurut Persepsi Petani Padi Di Desa Sangkub 4 Kecamatan Sangkub Kabupaten Bolaang Mongondow Utara - syamsir; Abidin, Zainal; Jafar, Muh Iqbal; Damogalad, Rita (JURNAL LITBANG PROVINSI JAWA TENGAH, 2024)
Agricultural extension is a task given to someone by the agricultural service with their respective target areas with the Agricultural Extension Center (BPP) as the coordinator. In the context of agricultural development in Indonesia, agricultural extension workers play an important role in transferring knowledge and technology to farmers. the purpose of this study was to determine the role of agricultural extension according to the perceptions of rice farmers in Sangkub 4 Village, Sangkub District, North Bolaang Mongondow Regency. This research was conducted in Sangkub 4 Village, Sangkub District, North Gorontalo Regency from March to May 2022. The data collection method used was observation and interview methods with a questionnaire guide using qualitative analysis where the sample of respondents was 63 rice farmers. The results showed that the first extension agent acts as a guide with a farmer's perception value of 2.56 and is included in the high category, the second is the extension agent's role as an organizer with a farmer's perception value of 2.52 which is also in the high category, the third is the extension agent's role as a technical trainer with a farmer's perception value of 2, 62 is included in the high category. So that overall the role of extension agents in rice farming in Sangkub 4 Village shows a perception value of 2.56 and is included in the high category or very involved.